2004
DOI: 10.1134/1.1868794
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of impedance, local density of states, and reflection in quantum chaotic systems with absorption

Abstract: We are interested in finding the joint distribution function of the real and imaginary parts of the local Green function for a system with chaotic internal wave scattering and a uniform energy loss (absorption). For a microwave cavity attached to a single-mode antenna the same quantity has a meaning of the complex cavity impedance. Using the random matrix approach, we relate its statistics to that of the reflection coefficient and scattering phase and provide exact distributions for systems with β=2 and β=4 sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
132
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(136 citation statements)
references
References 34 publications
4
132
0
Order By: Relevance
“…It was discovered first in 52 for the LDoS distribution in strictly one-dimensional systems using the Berezinskii technique 53 , it was later proved for systems of any dimensions in the framework of the nonlinear supersymmetric sigma model 54 . Later works 55 showed that (A3) is valid under very general conditions in both localized and extended phases. It is generally believed that the symmetry (A3) is exact in disordered (chaotic) systems where the phase of wave function is completely random.…”
Section: Discussionmentioning
confidence: 99%
“…It was discovered first in 52 for the LDoS distribution in strictly one-dimensional systems using the Berezinskii technique 53 , it was later proved for systems of any dimensions in the framework of the nonlinear supersymmetric sigma model 54 . Later works 55 showed that (A3) is valid under very general conditions in both localized and extended phases. It is generally believed that the symmetry (A3) is exact in disordered (chaotic) systems where the phase of wave function is completely random.…”
Section: Discussionmentioning
confidence: 99%
“…Support for some of Mello's reasoning was presented by P.W. Brouwer [9], who pointed out that also the statement is strictly true within a Lorentzian matrix ensemble, where it holds for any k ≤ n, and in [19], [20,Ch.IV] and [21, App. A] using supersymmetric calculations on other GXE ensembles in the large n limit.…”
Section: Introductionmentioning
confidence: 97%
“…[17,18] a symmetry relation for the LDOS distribution function (and thus, for the LDOS moments) in the Wigner-Dyson symmetry classes was derived: P(ν) = ν −q * −2 P(ν −1 ), ν q = ν q * −q , (…”
mentioning
confidence: 99%